Teaching with an adaptive technology: Data, acceptance and change - Jørnø, Rasmus Leth; Nortvig, Anne-Mette; Andersen, Bjarke (Proceedings of the International Conference on Networked Learning, 2024)
In this paper we present the first findings from a 4 year longitudinal study that investigates the interplay between an adaptive learning technology and educators and students in a nurse education in Denmark. With inspiration from grounded theory we analyse data from 14 hours of classroom observations supplemented by educator interviews, student surveys and mini interviews with students. In the paper we focus on the role of a new technology in the classroom: we ask how data reports from an adaptive learning technology influence educators’ preparations for classroom activities, and we ask how students' technology acceptance evolves over time. Analyzing our data we see three main themes emerge that contributes to answer the research question: Interpretative inclinations: The adaptive technology contributes to planning the lessons with a recurring inclination in practice: wrong answers lead to more educator presentations, and correct answers lead to student-centred group work during class. Implicit comparisons: The use of data reveals the educator’s expectations and assumptions when she implicitly compares the data on the students with her intuition, and when she compares the technology with the physical book. The implicit comparisons make the use of data challenging for the educator. Reverse adoption: The students find it hard to grasp the intention of the adaptive technology, but they accept and learn to adapt and appreciate it over time. In contrast to e.g. Rogers’ technology acceptance theory we find that the adaptive learning technology cannot be evaluated per se: in order to describe how a learning technology is accepted and what role it comes to play in an educational context, the parameter of time is mandatory to include in the research design.